Mapping Computational Thinking Skills Through Digital Games Co-Creation Activity Amongst Malaysian Sub-urban Children Sub-urban Children - Mohd Kamal, Othman; Syazni, Jazlan; Fatin Afiqah, Yamin; Shaziti, Aman; Fitri Suraya, Mohamad; Nurfarahani, Norman Anuar; Abdulrazak Yahya, Saleh; Ahmad Azaini, Abdul Manaf (SAGE Publishing, 2022)
This study investigates how digital game co-creation promotes Computational Thinking (CT) skills among children in sub-urban primary schools. Understanding how CT skills can be fostered in learning programming concepts through co-creating digital games is crucial to determine instructional strategies that match the young students’ interests and capacities. The empirical study has successfully produced a new checklist that can be used as a tool to describe the learning of CT skills when children co-create digital games. The checklist consists of 10 core CT skills: abstraction, decomposition, algorithmic thinking, generalisation, representation, socialisation, code literacy, automation, coordination, and debugging. Thirty-six 10–12 year-olds from sub-urban primary schools in Borneo participated in creating games in three separate eight-hour sessions. In addition, one pilot session with five participants was conducted. The game co-creation process was recorded to identify and determine how these young, inexperienced, untrained young learners collaborated while using CT skills. Analysis of their narratives while co-creating digital games revealed a pattern of using CT while developing the games. Although none of the groups demonstrated the use of all ten CTs, conclusively, all ten components of the CT were visibly present in their cocreated digital games.